"Reducing Disparities Between English And Chinese: A Comprehensive Examination Of The Elements Promoting Overall Positive Translation Quality And Their Relation To Cultural Sensitivity In Language" (Cuestiones de Fisioterapia, 2023)
The process of translation is of the highest relevance for the development of effective intercultural communication because it facilitates the transfer of meaning across a broad variety of cultural settings and languages. This is why translation is so important. Consequently, the process of translation is an undertaking that is of exceptional significance. The incapacity of persons who come from various cultural and linguistic backgrounds to engage with one another in an effective manner may have significant ramifications for all those who are involved who are involved in the situation. In addition to having a significant influence on the communication that takes place across international boundaries, the process of translating has a significant impact on a range of aspects of day-to-day operations. As a result of the findings of the study, those who have a personal interest in the subject matter that is being examined ought to find the findings to be intriguing. The findings of this study provide a second function, in addition to the information that they teach and the amusement that they provide to persons who are not proficient in translating. Educators and organisations that are seeking to enhance professional translation training get this material with the intention of providing them with knowledge that may be beneficial in the future. In addition to drawing attention to the obligation that translators have to give correct translations, the primary objectives of the endeavour are to create methods that will help translators to carry out this work with greater success in the past, as well as in the future.